2023
DOI: 10.11606/s1518-8787.2023057004449
|View full text |Cite
|
Sign up to set email alerts
|

Gravidez não planejada no Brasil: estudo nacional em oito hospitais universitários

Abstract: OBJETIVO: Estimar a prevalência de gestação não planejada (GNP) em oito hospitais públicos universitários, distribuídos nas cinco regiões que compõem o Brasil. MÉTODOS: Análise secundária de um estudo transversal multicêntrico nacional, realizado em oito hospitais universitários públicos, entre 1º de junho e 31 de agosto de 2020, no Brasil. Amostra por conveniência incluindo mulheres que deram à luz em período de sessenta dias consecutivos e atenderam aos seguintes critérios: maiores de 18 anos; idade gestacio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This percentage is lower than that in other countries, such as Ethiopia (26%), Sweden (31%), and Brazil (67%). [22][23][24] This is because most study participants live in the city and have good socioeconomic status and easy, free access to health care; these factors can explain the lower prevalence compared to other counties.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is lower than that in other countries, such as Ethiopia (26%), Sweden (31%), and Brazil (67%). [22][23][24] This is because most study participants live in the city and have good socioeconomic status and easy, free access to health care; these factors can explain the lower prevalence compared to other counties.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of unintended pregnancy and hesitancy to become pregnant among the study population was 17.6% and 19.4%, respectively; this is low compared to other counties such as Ethiopia, 26%, Sweden, 31%, and Brazil, 67%. [15][16][17] This prevalence is considered low compared to the study conducted in Riyadh, Saudi Arabia, in 2014, which showed a prevalence of 53%. [18] Marriage is a legal and cultural prerequisite for having children in Saudi Arabia, and having children outside this frame is rare or underreported.…”
Section: Discussionmentioning
confidence: 99%